1996
DOI: 10.1159/000174044
|View full text |Cite
|
Sign up to set email alerts
|

Is the Increase in Renal Papillary Phospholipid Biosynthesis a Protective Mechanism against Injury?

Abstract: Mercuric chloride (HgCl2) is a well-known renal toxic that causes acute renal failure. The effect of HgCl2 treatment and the protection by thyroxine were studied in rat renal papilla (P), outer medullary inner stripe (OMIS), outer medullary outer stripe (OMOS) and cortical phospholipids (PhLs). HgCl2 brought about an increase in the total phospholipid content in P and OMIS but a drop in OMOS and cortex. Only phosphatidylcholine (PtdCho) and phosphatidylethanolamine (PtdEtn) acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…For propidium iodide staining, the fi xed cells were washed once with PBS and from our laboratory demonstrated that the inner renal medulla has the most-active phospholipid synthesis and membrane turnover of all kidney zones ( 24 ). We have demonstrated that the ability of the inner renal medulla to renew the phospholipidic constituents of cell membranes is a defense mechanism against diverse injuries (25)(26)(27). We have speculated that such an active phospholipid metabolism in renal medullary cells is a consequence of the high interstitial osmolality, but we did not confi rm this hypothesis.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…For propidium iodide staining, the fi xed cells were washed once with PBS and from our laboratory demonstrated that the inner renal medulla has the most-active phospholipid synthesis and membrane turnover of all kidney zones ( 24 ). We have demonstrated that the ability of the inner renal medulla to renew the phospholipidic constituents of cell membranes is a defense mechanism against diverse injuries (25)(26)(27). We have speculated that such an active phospholipid metabolism in renal medullary cells is a consequence of the high interstitial osmolality, but we did not confi rm this hypothesis.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Consequently, this increase in biosynthesis might be a reflection of phospholipid renewal. We propose that such a renewal of phospholipids represents a protective mechanism to preserve membrane homeostasis in the face of a metabolic insult, as we have previously shown for a model of acute renal failure [7]. …”
Section: Discussionmentioning
confidence: 94%
“…For each experiment, 5 mg of tissue slices (0.5 mm thick) from control or diabetic rats were collected in 0.25 ml of 10 m M Tris/HCl solution (pH 7.4) containing electrolytes and 5 m M glucose [7]. Samples were incubated at 37°C with 14 mCi of [ 32 P]-sodium orthophosphate in a metabolic shaking bath, as described previously [7]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations